Same sun here - House, Silas, 1971-; Vaswani, Neela, 1974- (Candlewick Press, 2013)
Writing to each other as pen pals, Meena, an Indian immigrant living in New York, and River, a Kentucky coal miner's daughter, discover common ground between them and rely on their friendship to work through the difficult situations in their lives.